Electrical stimulation rate effects on speech perception in cochlear implants. - Arora K; Dawson P; Dowell R; Vandali A (International Journal of Audiology, 2009)
The objective of this study was to explore cochlear implant users' speech perception performance in quiet and in noise for low to moderate stimulation rates. Eight postlingually deaf adult users of the Nucleus CI24 cochlear implant (contour electrode array) using the ESPrit 3G speech processor participated in this study. Monosyllabic word recognition in quiet and sentence perception in noise was evaluated for low to moderate stimulation rates of 275, 350, 500, and 900 pulses-per-second/channel (pps/ch). All four stimulation rate programs were balanced for loudness. A repeated ABCD experimental design was employed. Take home practice was provided with each stimulation rate. Subjects also responded to a comparative questionnaire to examine their rate preference for a variety of listening situations. Results for six of the eight subjects showed no significant effect of rate for monosyllables in quiet. However, results for the sentence test in noise demonstrated improvements with 500 or 900 pps/ch stimulation rates in seven out of the eight subjects. Although there was not a close relationship between each subject's subjective preference and the rate program that provided best speech perception, most subjects indicated a preference for 500 pps/ch rate in noise.